2012
DOI: 10.1186/2193-1801-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Unified approach to growth and aging in biological, technical and biotechnical systems

Abstract: Complex systems, in many different scientific sectors, show coarse-grain properties with simple growth laws with respect to fundamental microscopic algorithms. We propose a classification scheme of growth laws which includes human aging, tumor (and/or tissue) growth, logistic and generalized logistic growth and the aging of technical devices. The proposed classification permits to evaluate the aging/failure of combined new bio-technical “manufactured products”, where part of the system evolves in time accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The PDFs for these distributions are given in Appendix A. These distributions are widely used in reliability theory [5, 49, 55], survival analysis [43], and studies of aging and lifespan for both mechanical and biological systems using a reliability theory approach [6, 10, 25, 26, 33]. Although the Weibull is widely used as a failure distribution [5], aside from the papers by Friese et al [22, 23], ours is the only use of the Weibull as an RBC lifespan distribution to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The PDFs for these distributions are given in Appendix A. These distributions are widely used in reliability theory [5, 49, 55], survival analysis [43], and studies of aging and lifespan for both mechanical and biological systems using a reliability theory approach [6, 10, 25, 26, 33]. Although the Weibull is widely used as a failure distribution [5], aside from the papers by Friese et al [22, 23], ours is the only use of the Weibull as an RBC lifespan distribution to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…1 e), as those reported by Regen ( 1941 ) in A. virginica who interpreted the presence of triads as the possible non division of one of the megaspores of the dyad to enter meiosis II. Gomez-Rodríguez et al ( 2012 ) observed the formation of triads in the pollen microsporogenesis of A. tequilana and A. angustifolia which are formed by a mechanism where a failure in meiosis II in a cell of the dyad prevented the formation of cell wall in the daughter nuclei, which finally are restored, leading to the formation of a 2n microspore and two n microspores (unreduced gametes).…”
Section: Resultsmentioning
confidence: 99%
“…For technical devices, the previous classification scheme has been generalized since the specific growth rate of Weibull law has a power dependence on t which is not reproduced by equation (4). The behavior α f (t) ; t n , with n positive integer, corresponds to terms O ( n n 1 a -) ( ) in the expansion of Φ(α) and therefore for a general classification scheme of the specific growth/aging/failure rate of biological and technical systems one has to consider [9]:…”
Section: Classification Of Growth Lawsmentioning
confidence: 99%
“…the exponential growth, can be neglected if one considers the GL, the generalized logistic or more complex growth laws for the biological systems (there is no problem to include this term in the expansion); (c) the first sum in the expansion has fractional powers. As a by-product of the proposed classification scheme one can easily evaluate the aging/failure of combined new bio-technical 'manufactured products' [9].…”
Section: Classification Of Growth Lawsmentioning
confidence: 99%
See 1 more Smart Citation